The Tendency of the News on Kompas and Republika Newspaper about Basuki Tjahaja Purnama Nomination as Governor of Jakarta at 2017 Election - Sriadi Lintang Kusumadewi; Primada Qurrota Ayun, S.I.Kom, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
At the Jakarta governor election in 2017, racial issues was predicted to be a topic that will following Basuki Tjahaja Purnama in his candidacy for governor. That issue can not be separated from the role of the mass media to influence public opinion. Due to the influence, media are required to always objective in conveying information to the public. This research is descriptive research with quantitative content analysis method. The purpose of this study was to determine the tendency of the news in two national newspapers, namely, Kompas and Republika regarding nomination Tjahaja Basuki Purnama as Jakarta governor in the elections in 2017. This can be seen in the presentation of news, news direction, and factuality balance in their news reporting. Researchers make coding sheet from two coders the results are used to calculate reliability. Judging from the content categories of news, from the results of the analysis unit, the tendency of news about the nomination Basuki Purnama Tjahaja in Kompas daily more neutral, whereas the negative trend in the Republika daily news about Tjahaja Basuki Purnama. By results of different test by using chi square formula no significant difference between both media, it is because the number of samples studied is not too much and both these media has the same characteristics.